PELAKSANAAN BIMBINGAN REMAJA USIA SEKOLAH YANG MENJADI PROBLEMATIKA KANTOR URUSAN AGAMA z DALAM MENCEGAH PERNIKAHAN DINI (Studi Kasus Di KUA Kec.Mojosari Kab.Mojokerto) - Ahmad Syarif Hidayatulloh; H. Ahmad Faruq (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The School Age Adolescent Guidance Program (BRUS) in Mojosari District, which was initiated by the Office of Religious Affairs (KUA), aims to provide guidance and education to school age adolescents regarding various aspects of life, including marriage, reproductive health and self-development, although KUA has Collaborating with several educational institutions, the BRUS program still faces several obstacles, such as: 1) Lack of certified and trained religious instructors to implement the BRUS program, 2) The large number of schools and teenagers who are the targets of the program, making it difficult for the KUA to organize schedules and reaching all parties, 3) Limited time to implement the program thoroughly and comprehensively. KUA Mojosari's efforts in implementing the BRUS program should be appreciated. Even though there are still several obstacles, this program is expected to provide significant benefits for school-aged teenagers in Mojosari District. From the results of this research, it can be concluded that the implementation of the school-aged youth guidance program in Mojosari District still needs to be improved. By overcoming existing obstacles, it is hoped that this program can run more effectively and be beneficial for teenagers in Mojosari District.